Enhancing Writing Skills through Literary Texts the C ase of Writing Classes in Nov 1 st , H igh S chool in Laghouat - Sahraoui ,Meriem; Roummane,Imane (University of Ammar Theledji -Laghouat, 2021)
Literature is the creative, original and specific use of language in a way which makes it different from that of practical everyday language. This is accomplished through word manipulation, alliteration, assonance, and other rhetorical techniques. With this in mind, the aim of this research is to incorporate reading literary texts into English as a foreign language in order to assist students develop their reading and subsequently their writing skills in their writing classes. In so doing, they will likely be able to communicate and express their beliefs and ideas more efficiently. The findings of this paper reveal that the students' proficiency in writing in English is low, and that the use of the literary text as a learning platform, or tool, can help students improve their writing and language skills